Mo. Rev. Stat. 224, ch. 24, art. 2, §§ 1274-1278 (1879) - (:unkn) unknown (My University, 1879)
If any person shall carry concealed, upon or about his person, any deadly or dangerous weapon, or shall go into any church or place where people have assembled for religious worship, or into any school room or place where people are assembled for educational, literary or social purposes, or to any election precinct, on any election day, or into any court room during the sitting of court, or into any other public assemblage of persons met for any lawful purpose, other than for militia drill or meetings called under the militia law of this state, having upon or about his person any kind of firearms, bowie-knife, dirk, dagger, slung-shot, or other deadly weapon, or shall, in the presence of one or more persons, exhibit any such weapon in a rude, angry or threatening manner, or shall have or carry any such weapon upon or about his person when intoxicated or under the influence of intoxicating drinks, or shall, directly or indirectly, sell or deliver, loan or barter to any minor, any such weapon, without the consent of the parent or guardian of such minor, he shall, upon conviction, be punished by a fine of not less than five nor more than one hundred dollars, or by imprisonment in the county jail not exceeding three months, or by both such fine and imprisonment. (Laws 1874, p. 43; laws 1875, p. 50, and laws 1877, p. 240,.amended.)
Keywords: BRANDISHING; CARRY - CERTAIN PUBLIC PLACES; CARRY - CONCEALED; CARRY - DANGEROUS PERSONS; SENSITIVE PLACES; TRANSFER - MINORS